Mediterranean Diet Combined With a Low-Carbohydrate Dietary Pattern in the Treatment of Overweight Polycystic Ovary Syndrome Patients - Mei, Shanshan; Ding, Jie; Wang, Kaili; Ni, Zhexin; Yu, Jin (Frontiers in Nutrition, 2022)
Objectives To determine the therapeutic effect of a Mediterranean diet (MED) combined with a low-carbohydrate (LC) dietary model in overweight polycystic ovary syndrome (PCOS) patients. Methods In this 12-week randomized controlled clinical trial, 72 overweight patients with PCOS were randomly assigned to one of two energy-restricted dietary models: the MED/LC diet or the Low fat (LF) diet. After the intervention, the number of the two groups returned to normal menstruation was counted. Body weight, body mass index (BMI), waist circumference, waist-hip ratio (WHR), body fat percentage (BF%), serum fasting insulin(FINS), fasting plasma glucose(FPG), insulin resistance index (HOMA-IR), quantitative insulin sensitivity index (QUIKI), total cholesterol (TC) and high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), triglyceride (TG), total testosterone (TT), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and prolactin (PRL) were compared between 2 groups before and after intervention. Results MED/LC group had more significant reduction trend in weight (−6.10 ± 1.52 kg vs −4.79 ± 0.97 kg, P < 0.05), BMI (−2.12 ± 0.57 kg/m2 vs −1.78 ± 0.36 kg/m2, P < 0.05), WC (−6.12 ± 5.95 cm vs −3.90 ± 1.58 cm, P < 0.05), WHR (−0.06 ± 0.02 vs −0.03 ± 0.02, P < 0.05), BF% (−2.97% ± 1.78% vs −1.19% ± 0.91%, P < 0.05), TT (−0.20 ± 0.24 ng/mL vs 0.08 ± 0.11 ng/Ml, P < 0.001), LH (−5.28 ± 3.31 mIU/mL vs −3.39 ± 3.64 mIU/mL, P < 0.05), and LH/FSH (−1.18 ± 0.75 vs -0.66 ± 1.05, P < 0.05) compared with the LF group. In addition, FPG (0.05 ± 0.38 mmol/mL vs -0.50 ± 1.01 mmol/mL, P < 0.001), FINS (−4.88 ± 6.11 μU/mL vs −8.53 ± 5.61 μU/mL, P < 0.01), HOMA-IR index (−1.11 ± 1.51 vs −2.23 ± 0.25, P < 0.05), and QUIKI index (0.014 ± 0.016 vs 0.028 ± 0.019, P < 0.05) decreased significantly in the MED/LC group compared with the LF group. Comparing the changes in lipid parameters between the two groups (LF vs MED/LC), significant differences in TG (−0.33 ± 0.32 mmol vs −0.76 ± 0.97 mmol, P < 0.05), TC (−0.40 ± 1.00 mmol vs −1.45 ± 2.00 mmol, P < 0.05), and LDL-C (−0.41 ± 1.05 mmol vs −0.73 ± 0.76 mmol, P < 0.05) were observed. Conclusion The results of this study suggest that the MED/LC diet model is a good treatment for overweight PCOS patients, significantly restoring their menstrual cycle, improving their anthropometric parameters and correcting their disturbed endocrine levels, and its overall effectiveness is significantly better than the LF diet model. Therefore, this study recommends that the MED/LC diet model can be used in the clinical treatment of patients with overweight PCOS.